2019
DOI: 10.1161/circep.118.006884
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Association Study in Multigenerational Kindreds With Vasovagal Syncope

Abstract: Background: Several studies suggest that vasovagal syncope has a genetic origin, but this is unclear. We assessed whether plausible gene variants associate with vasovagal syncope. Methods: We studied 160 subjects in 9 kindreds comprising 82 fainters and 78 controls. The diagnosis was ascertained with the Calgary Syncope Score. Common genetic variants were genotyped for 12 genes for vascular signaling, potassium channels, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 37 publications
0
22
3
2
Order By: Relevance
“…However, the control population was syncope patients with negative tilt responses, not unaffected controls. Furthermore, neither we (18) nor others (25, 31) detected an association of the ADRB1 1165G>C alleles with the clinical vasovagal phenotype when compared with unaffected control subjects.…”
Section: Candidate Gene Analysescontrasting
confidence: 74%
See 1 more Smart Citation
“…However, the control population was syncope patients with negative tilt responses, not unaffected controls. Furthermore, neither we (18) nor others (25, 31) detected an association of the ADRB1 1165G>C alleles with the clinical vasovagal phenotype when compared with unaffected control subjects.…”
Section: Candidate Gene Analysescontrasting
confidence: 74%
“…Most candidate gene studies of vasovagal syncope compared patients with positive tilt tests to those with negative tilt tests; in essence, a surrogate biomarker. We took a complementary approach by directly testing the association of 12 candidate gene alleles with clinical vasovagal syncope in 7 kindreds (18). The advantages of this approach are that we are studying clinical presentations and not surrogate markers, and kindred studies reduce the background variability in both genetic and environmental influences.…”
Section: Candidate Gene Analysesmentioning
confidence: 99%
“…A recent genetic association study in VVS took a slightly different approach. Instead of just looking at the overall cohort of 160 participants, the investigators probed 12 distinct candidate genes by sex [8]. There was no significant association for nine of the 12 candidate genes.…”
mentioning
confidence: 99%
“…Twin studies and small genome-wide association studies hint at genetic loci [8]. Candidate gene studies have identified adrenergic signalling pathways that correlate with tilt test outcomes, and a study [9] of seven kindreds identified three candidate genes associated with serotonin and dopamine signalling. Studies of vasovagal syncope, however, have focused on European heritage populations, either in Europe [10][11][12][13] or the Americas [6,9,[14][15][16].…”
mentioning
confidence: 99%
“…Finally, are the same alleles associated with clinical vasovagal syncope in all the Malaysian populations as in European-Canadians? This is critical, because these three genes-the serotonin transporter, the serotonin 1A receptor, and catecholamine O-methyltransferase-have different effects on syncope likelihood in men and women [9]. Tan et al [4] carefully documented the incidence of syncope in several populations many thousands of years apart, and in doing so lay the groundwork for fundamentally important work in the future.…”
mentioning
confidence: 99%